Negative Pressure Wound Therapy in the Head and Neck: A Summary of Uses and Application Techniques - Liebman, Robert Michael; Hanubal, Krishna S.; Dziegielewski, Peter T. (Seminars in Plastic Surgery, 2022)
Negative pressure wound therapy (NPWT) has had an expanded role in the management of complex wounds including its increasing use for complex wounds in the head and neck region. Challenges for use in the head and neck region include variations in surface topography and the proximity of sensitive mouth, nose, ear, eye, and tracheal openings. Despite these challenges, NPWT has been used in the head and neck immediately following free flap surgery, to prepare wounds for skin grafting or local flaps, to treat orocutaneous and pharyngocutaneous fistulas, to treat necrotizing and deep neck space infections, to temporize and palliate, and to treat chronic wounds with exposed bone and hardware among others. This review demonstrates the proven track record of successful uses of NPWT in the aforementioned scenarios, provides suggestions to improve efficacy, as well as an algorithm for use in certain clinical situations.
Keywords: negative pressure wound therapy; head and neck; fistula; necrotizing fasciitis